A Systematic Study of the Stability of Enzyme/Zeolitic Imidazolate Framework‐8 Composites in Various Biologically Relevant Solutions. Issue 43 (19th November 2020) - Gao, Yuan; Doherty, Cara M.; Mulet, Xavier
Abstract: Metal organic frameworks (MOFs) have been used to encapsulate numerous enzymes. This study has encapsulated two enzymes in zeolitic imidazolate framework‐8 (ZIF ‐8 ) and examined the structural stability of the enzyme@ZIF‐8 composites in solutions of various biologically relevant agents ( i. e . amino acids, proteins, organic acids, organic/inorganic buffers, surfactants, polymers, carbohydrates and salts). Many of the agents were found to completely dissolve the composites or severely damage their structural integrity, causing the release of the enzymes from the composites. These agents plausibly exerted their destabilizing effects on the composites by interactions with zinc or by complexation with the enzymes in the enzyme@ZIF‐8 composites. Notably, Tris and HEPES buffers were found to be supportive of the composites in the short term. The results show the need to improve the stability of the enzyme@ZIF‐8 systems for certain applications and suggest triggered release of the encapsulated biomolecules from the porous matrix. Abstract : Beware: the composites of enzymes@ZIF ‐8 are unstable in solutions The metal‐organic framework ZIF ‐8 has been used to encapsulate numerous enzymes. However, the composites are easily degraded or even destroyed in many biologically relevant solutions, leading to the release of the encapsulated enzymes. Chemicals that can complex with zinc or proteins, or form insoluble salts with zinc are particularly harmful. The structural instability must be kept in mind when pursuing applications of enzyme@ZIF‐8 composites.